Adjunctive hyperbaric oxygen therapy and negative pressure wound therapy for hard-to-heal wounds: a systematic review and meta-analysis. - Yang, Liehao; Kong, Jiao; Xing, Yunlong; Pan, Lingfeng; Li, Caihong; Wu, Zhuoxia; Li, Mingxi; Zhang, Lianbo (Journal of Wound Care, 2024)
Objective: Negative pressure wound therapy (NPWT) and hyperbaric oxygen therapy (HBOT) have been widely used in the treatment of hard-to-heal (chronic) wounds, but there is still a lack of sufficient evidence for their combined use for the treatment of hard-to-heal wounds. This systematic review aimed to identify the clinical efficacy and safety of adding adjunctive HBOT to NPWT for hard-to-heal wounds. Method: Embase, PubMed, Cochrane Library, Web of Science, China National Knowledge Infrastructure and Wanfang were searched from the establishment of the database to March 2022. The literature was screened according to the inclusion criteria and exclusion criteria. We assessed the quality of each included study with the Cochrane Collaboration Risk of Bias tool and Newcastle–Ottawa Scale. A meta-analysis was performed using R programming software version 4.1.0 (R Project for Statistical Computing, US). The PRISMA 2020 guidelines were used to report data from systematic reviews and meta-analysis. Results: A total of 15 studies were identified, including nine randomised clinical controlled trials and six retrospective studies. Meta-analysis results showed that NPWT combined with HBOT had better outcomes compared with the NPWT alone with regards to: wound healing rate (odds ratio (OR)=6.77; 95% confidence interval (Cl): 3.53–12.98; p<0.0001); bacterial positive rate of wound (OR=0.16; 95% CI: 0.05–0.55; p=0.0037); wound healing time (mean difference (MD)= –3.86; 95% Cl: –5.18 – –2.53; p<0.0001); wound area (standardised mean difference (SMD)=1.50; 95% Cl: 0.35–2.65; p=0.0104); hospitalisation time (MD= –3.14; 95% Cl: –4.93 – –1.36; p=0.005); and hospitalisation cost (OR= –202.64; 95% Cl: –404.53 – –0.75; p=0.0492). There was no significant difference in pain score (MD= –0.43; 95% Cl: –1.15–0.30; p=0.25). Conclusion: The findings of this study demonstrated that adjunctive HBOT with NPWT is safe and effective in the treatment of hard-to-heal wounds. However, these findings should be interpreted with great caution given the limitations of the studies included.